Secretion of poly-γ-glutamic acid by Bacillus atrophaeus NX-12 enhanced its root colonization and biocontrol activity - Xue, Jian; Tong, Tong; Wang, Rui; Qiu, Yibin; Gu, Yian; Sun, Liang; Xu, Hong; Lei, Peng (Frontiers in Microbiology, 2022)
Bacillis are used as biocontrol agents (BCAs) against phytopathogens and most of them can produce poly-γ-glutamic acid (γ-PGA) as one of the major extracellular polymeric substances (EPSs). However, the role of γ-PGA in plant biocontrol is still unclear. In this study, Bacillus atrophaeus NX-12 (γ-PGA yield: 16.8 g/L) was screened, which formed a strong biofilm and has been proved to be a promising BCA against Cucumber Fusarium Wilt. Then the γ-PGA synthesis gene cluster pgsBCA was knocked out by CRISPR-Cas9n. Interestingly, the antifungal ability of γ-PGA synthetase deficient strain NX-12Δpgs (γ-PGA yield: 1.65 g/L) was improved in vitro while the biocontrol ability of NX-12Δpgs was greatly diminished in situ. Data proved that γ-PGA produced by NX-12 contributes to the biofilm formation and the rhizosphere colonization, which effectively improved biocontrol capability. Taken together, these findings prove the mechanism of γ-PGA promotes the colonization of NX-12 and thus assists in controlling plant diseases, which highlight the key role of γ-PGA produced by BCA in biocontrol.